1995
DOI: 10.1164/ajrccm.152.2.7633731
|View full text |Cite
|
Sign up to set email alerts
|

A community study of snoring and sleep-disordered breathing. Prevalence.

Abstract: We conducted a study of the prevalence of sleep-disordered breathing in subjects derived from a random sample of the population. A total of 2,202 subjects 35 to 69 yr of age were approached. Four hundred forty-one answered a questionnaire concerning their sleep symptoms, general health, and habits such as alcohol consumption, and they were monitored for sleep-disordered breathing (SDB). The sample was biased in favor of snorers and those with other subjective sleep complaints. Fifty-six percent of the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
5
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(128 citation statements)
references
References 19 publications
6
112
5
4
Order By: Relevance
“…Even though a higher prevalence of sleep apnoea has been reported in an Australian study, 37 the prevalence of SDB was high compared with most other population based studies. This is partly explained by the fact that the population was biased by oversampling of hypertensive subjects and, as the non-hypertensive controls were matched for BMI, there was also an oversampling of overweight subjects in the control group.…”
Section: Discussioncontrasting
confidence: 59%
“…Even though a higher prevalence of sleep apnoea has been reported in an Australian study, 37 the prevalence of SDB was high compared with most other population based studies. This is partly explained by the fact that the population was biased by oversampling of hypertensive subjects and, as the non-hypertensive controls were matched for BMI, there was also an oversampling of overweight subjects in the control group.…”
Section: Discussioncontrasting
confidence: 59%
“…Patients with age less than 30 and more than 60, those with history of surgery to the nose, nasopharynx or throat and those with neurological problems were excluded. Based on the previous studies, the prevalence of OSAS was found to be 3.6% 5 with 5% level of significance and 0.6% precision, a sample of 40 patients were recruited for the study. A detailed history and general examination which included measurement of height, weight, chest, neck, waist and hip circumference were taken.…”
Section: Methodsmentioning
confidence: 99%
“…The physiopathology of OSAHS is multifactorial and derives in part from upper airway or craniofacial anatomical alterations associated with alterations of the neuromuscular pharynx (2). The highest prevalence is among males and in the 40-and 50-year-old groups (3). Other factors such as obesity and upper airway or craniofacial anatomical alterations have also been correlated with the disease (2).…”
Section: Introductionmentioning
confidence: 99%